Immune system of the inner ear as a novel therapeutic target for sensorineural hearing loss - Okano, Takayuki (Frontiers in Pharmacology, 2014)
Sensorineural hearing loss (SNHL) is a common clinical condition resulting from dysfunction in one or more parts in the auditory pathway between the inner ear and auditory cortex. Despite the prevalence of SNHL, little is known about its etiopathology, although several mechanisms have been postulated including ischemia, viral infection or reactivation, and microtrauma. Immune-mediated inner ear disease has been introduced and accepted as one SNHL pathophysiology; it responds to immunosuppressive therapy and is one of the few reversible forms of bilateral SNHL. The concept of immune-mediated inner ear disease is straightforward and comprehensible, but criteria for clinical diagnosis and the precise mechanism of hearing loss have not been determined. Moreover, the therapeutic mechanisms of corticosteroids are unclear, leading to several misconceptions by both clinicians and investigators concerning corticosteroid therapy. This review addresses our current understanding of the immune system in the inner ear and its involvement in the pathophysiology in SNHL. Treatment of SNHL, including immune-mediated inner ear disorder, will be discussed with a focus on the immune mechanism and immunocompetent cells as therapeutic targets. Finally, possible interventions modulating the immune system in the inner ear to repair the tissue organization and improve hearing in patients with SNHL will be discussed. Tissue macrophages in the inner ear appear to be a potential target for modulating the immune response in the inner ear in the pathophysiology of SNHL.